Synthesis and Characterization of Sulfonamide-Containing Naphthalimides as Fluorescent Probes - Zhi-Wei Liu; Fan Liu; Chun-Tao Shao; Guo-Ping Yan; Jiang-Yu Wu (Molecules)
A tumor-targeting fluorescent probe has attracted increasing interest in fluorescent imaging for the noninvasive detection of cancers in recent years. Sulfonamide-containing naphthalimide derivatives (SN-2NI, SD-NI) were synthesized by the incorporation of N-butyl-4-ethyldiamino-1,8-naphthalene imide (NI) into sulfonamide (SN) and sulfadiazine (SD) as the tumor-targeting groups, respectively. These derivatives were further characterized by mass spectrometry (MS), nuclear magnetic resonance spectroscopy (1H NMR), Fourier transform infrared spectroscopy (FT-IR), ultraviolet–visible spectroscopy (UV), and a fluorescence assay. In vitro properties, including cell cytotoxicity and the cell uptake of tumor cells, were also evaluated. Sulfonamide-containing naphthalimide derivatives possessed low cell cytotoxicity to B16F10 melanoma cells. Moreover, SN-2NI and SD-NI can be taken up highly by B16F10 cells and then achieve good green fluorescent images in B16F10 cells. Therefore, sulfonamide-containing naphthalimide derivatives can be considered to be the potential probes used to target fluorescent imaging in tumors.